Enhancement of i-Learn : course information checker system / Muhammad Anuar Ridzwan Hashim - Ridzwan Hashim, Muhammad Anuar (2006)
This project is prepared for I-learn Center (i-LeC) that operates under the Academic Affair Division. The "Course Information Checker System" is created to reduce the burden that i-leam system administrator face in order to manage and maintain the content in the database used for i-learn portal. There are around 8000 course codes in database that covered all the courses taught by all faculties in UiTM. There are also around 8000 course information in the database because the number of course information is based on the number of course code available. By using this system, system administrator can reduce their time to check either the course information is complete or not by referring to the statistical data that the system generates. System administrator will also get accurate overview and understanding about the overview of the database content from the graph representations that are generated from the statistical data. With the use of internet programming method and combination of software such as Apache, MySQL, and PHP as a programming language, a module to check into the course info content has been build to check and categorize the course information based on their level of completion. The result then will be represented using graph form that was built using JpGraph. JpGraph is an Object-Oriented graph library that is fully coded using PHP language and provides a tool to generate and render graph and can be used with database.